Aktifitas Antioksidan dan Inhibitor Tirosinase Beberapa Stilbenoid dari Tumbuhan Moraceae dan Dipterocarpaceae yang Potensial untuk Bahan Kosmetik - Euis Holisotan Hakim; Yana Maolana Syah; Lia Dewi Juliawati; Didin Mujahidin (Jurnal Matematika & Sains, 2008)
In a drug discovery program to combat various diseases, many natural chemicals originating from Indonesian tropicalplants including Moraceae and Dipterocarpaceae have been investigated in our laboratory. These family of plants areknown as rich sources of stilbenoid type of compounds which have been shown to have various bioactivities, that arepotentially important in cosmetic bioindustry. In the course of our search for bioactive natural products from plants, wewere interested in the stilbenoid constituents of these plants. Thus, as part of this program, several stilbene derivativeswere successfully isolated from extracts of Morus macroura, a Moraceous plant locally named andalas, includingoxyresveratrol (1), lunularin (2) and new resveratrol dimers, namely andalasin A (3) and andalasin B (4). While,biotransformation of oxyresveratrol (1) using cell suspension culture of Solanum mammosum affordedtrans-oxyresveratrol-4-O-Î²-D-glucopyranoside (5). Similarly, some resveratrol derivatives have been isolated fromDipterocarpaceous plants, such as Shorea assamica, S. seminis, Vatica umbonata, and Dryobalanops oblongifolia.These species gave, among others, resveratrol (6), resveratrol-12-C-Î²-glucopyranoside (7), the resveratrol dimers(-)-Îµ-viniferin (8) and the new compound diptoindonesin A (9), in addition to resveratrol trimers (-)-Î±-viniferin (10), thenew compounds cis-diptoindonesin B (11) and trans-diptoindonesin B (12). Among these compounds oxyresveratrol (1),andalasin B (4), trans-oxyresveratrol-4-O-Î²-D-glucopyranoside (5), resveratrol (6), cis-diptoindonesin B (11) andtrans-diptoindonesin B (12) exhibited the most potent antioxidant activity [1,1-diphenyl-2-picrylhydrazil (DPPH)radical-scavenging activity]; moreover, andalasin A (3) have been reported to show a very strong tirosinase inhibitoractivity, thus valuable in cosmetic industry.